Effects of diet complexity and replacement of soybean meal on growth performance of weanling pigs - Baudon, E.C.; Llanes, N.; Hancock, Joe D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A total of 192 pigs (avg initial BW of 13.9 lb and avg initial age of 21 d) was used to determine the effects of complex diet formulations (with plasma protein and whey) in nursery diets with wheat gluten used to replace soybean meal. Treatments were arranged as a 2 x 2 factorial, with main effects of diet complexity (no animal plasma and 10% dried whey vs 7% animal plasma and 20% dried whey) and soybean meal (25% vs none). For d 0 to 14, the complex diet formulations increased ADG while replacement of the soybean meal with wheat gluten decreased ADG (P<0.001). Efficiency of gain was improved by 7% when plasma and whey were increased in the formulations (P<0.04) but not affected by deletion of soybean meal (P=0.15 or greater). When all the pigs were changed to a common Phase 2 diet (with soybean meal and without plasma) for d 14 to 28, ADG and ADFI were less for those pigs fed the more complex formulations during the first 14 d of the experiment (P<0.002). Overall (d 0 to 28), pigs fed diets with soybean meal for d 0 to 14 had greater ADG and ADFI, and pigs fed the diets with plasma and 20% whey had better feed/gain (P<0.007). In conclusion, complex formulations (i.e., with 7% plasma and 20% whey) for d 0 to 14 improved growth performance regardless of the absence or presence of soybean meal, and using wheat gluten to rid the Phase 1 diets of soybean meal was of no benefit.
Keywords: Nursery; Plasma; Whey; Soybean meal; Swine